Research progress on the metabolism and homeostatic regulation of arginine in oral-intestinal flora - SUN Yunran, YUE Yang, WU Haoze, ZHANG Mai, WANG-LUO Qianhui, CHENG Xiaogang (口腔疾病防治)
Dysbiosis can cause microenvironmental dysregulation, which can further lead to local or systemic diseases, such as caries, inflammatory bowel disease, obesity, and diabetes. Dysbiosis is primarily manifested as the disturbance of metabolic processes and products. Arginine plays an important role in various metabolic processes and homeostasis of the microbial flora and the host. This study aims to explore the potential therapeutic value of arginine and its metabolism and homeostasis regulation in diseases associated with oral-intestinal dysbiosis. Host and microbial homeostasis can be restored by regulating the composition or function of host microbiota, and arginine has been found to exhibit significant clinical potential in restoring host microbiota composition and function. For example, arginine can reduce the risk of caries by regulating the relative abundance of Streptococcus mutans and Streptococcus sanguineus. Additionally, arginine metabolism may play a therapeutic role in inflammatory bowel disease and obesity by regulating the relative abundance of Firmicutes and Bacteroidetes. In addition, supplementation of arginine and its metabolite polyamine has clinical prospects in the treatment of diabetic patients with ketoacidosis. Although studies have demonstrated the therapeutic role of arginine in oral, intestinal, and metabolism-related diseases, the specific mechanism is yet to be explored. In addition, further research is required to determine the optimal clinical dosage of arginine that can maintain microbiota homeostasis without causing any side effects.